Yield and yield components responses to plant density in cowpea grown in two savannah agro-ecologies in Nigeria - Namo, O.A.T.; Odesina, I.S.; Akpensuen, T.T.; Utoblo, O.; Boukar, O.; Ongom, P.O.; Oyebode, G.O. (2025)
Gap-filling is used to mitigate yield losses in different legumes. There is scanty information on this mechanism of yield compensation in the cowpea [Vigna unguiculata (L.)Walp]. This study investigated responses of yield and yield components to plant density in some accessions of cowpea at Minjibir and Shika locations. The randomized complete block design, in a split-plot arrangement in three replicates, was used. The main plots consisted of four plant densities, while the sub-plots consisted of six cowpea accessions. Results showed that plant density and environment affected yield and yield components. Total grain yield increased as plant density increased at both locations and was highest in the accession DANILA (1793.3 kg ha−1) at 99,999 plant ha−1 and lowest in the accession IT98K-205-8 (1100 kg ha−1) at 33,333 plants ha−1. Pod yield was positively correlated with total grain yield at Minjibir (0.267*) and Shika (0.917**) and when data were combined (0.990**). Shelling percentage was negatively correlated with total grain yield when data were combined (−0.610**). Significant positive correlation between total grain yield and 100-seed weight as well as biological yield was observed at Shika. Harvest index was positively correlated with total grain yield (0.407**) at Minjibir. The study concludes that erect accessions (IT93K-452-1 and IT98K-205-8) and semi-erect accessions (IT99K-573- 1-1 and IT08K-150-27) could be adopted for cultivation at 133,333 plants ha−1,while prostrate accessions (IT89KD-288 andDANILA) could be cultivated at 99,999 plants ha−1 at Minjibir. The accessions IT93K-452-1, IT98K-205-8, IT99K-573-1-1, and IT08K-150-27 could be cultivated at Shika, irrespective of plant density.